2021
DOI: 10.1017/ice.2021.523
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19) vaccine intentions and uptake in a tertiary-care healthcare system: A longitudinal study

Abstract: Objective Healthcare workers (HCWs) are a high priority group for COVID-19 vaccination and serve as sources for information for the public. This analysis assessed vaccine intentions, factors associated with intentions, and change in uptake over time in HCWs. Methods A prospective cohort study of COVID-19 seroprevalence was conducted with HCWs in a large healthcare system in the Chicago area. Participants completed surveys (November 25, 2020-January 9, 2021 and April 24-July 12, 2021) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…14 On the other hand, a study by Evans et al conducted on healthcare workers in the United States demonstrated that 59.7% of those who previously reported no intention of getting vaccinated against COVID-19 and 90.6% of those who had previously been unsure were vaccinated by follow-up six months later. 30 These results are comparable to ours. The Understanding America Study (UAS), a repeated survey of a probabilistic Internet panel of adults in the United States, found that non-Hispanic Asian people were more likely to have increased likelihood of receiving a COVID-19 vaccine than non-Hispanic White people.…”
Section: Discussionsupporting
confidence: 88%
“…14 On the other hand, a study by Evans et al conducted on healthcare workers in the United States demonstrated that 59.7% of those who previously reported no intention of getting vaccinated against COVID-19 and 90.6% of those who had previously been unsure were vaccinated by follow-up six months later. 30 These results are comparable to ours. The Understanding America Study (UAS), a repeated survey of a probabilistic Internet panel of adults in the United States, found that non-Hispanic Asian people were more likely to have increased likelihood of receiving a COVID-19 vaccine than non-Hispanic White people.…”
Section: Discussionsupporting
confidence: 88%
“…Maciuszeket al [37] found that those with lower initial vaccine attitudes had higher increases in vaccination intention than those who were consistently acceptant. Conversely, Evans et al [34] did not find any significant trait differences among initially hesitant healthcare workers who did and did not get vaccinated by follow-up. Although these studies measure shifting intentions, they either focus on socio-demographic predictors alone or treat behavioural beliefs as static.…”
Section: Literature Reviewmentioning
confidence: 87%
“…Waszkiewicz et al [33] surveyed respondents about their vaccination intention at two time points and asked those who were previously vaccine hesitant to disclose the reasons behind their shifting mindset; main factors were increased concern about health and safety and a desire to travel. Evans et al [34] , Harada & Watanabe [35] , Hyland et al [36] , and Maciuszeket al [37] also surveyed respondents over time, identifying potential traits or beliefs at one wave that were associated with changes in vaccination intention at a later wave. Harada & Watanabe [35] found that those who shifted from hesitant to acceptant had higher COVID-19-related anxiety and lower concern for adverse vaccine side effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Willingness to vaccinate has also increased over time [58,81,139] suggesting that additional HCWs may vaccinate with time. One study noted that 59.7% of HCWs who had been unsure about vaccination were later vaccinated by a 6-month follow-up [255]. However, it is unclear in what timeframe this will occur [255].…”
Section: Towards the Futurementioning
confidence: 99%
“…One study noted that 59.7% of HCWs who had been unsure about vaccination were later vaccinated by a 6-month follow-up [255]. However, it is unclear in what timeframe this will occur [255]. Furthermore, the benefits of allowing HCWs to delay vaccination or continue to seek exemptions must be weighed with the continued risks of being unvaccinated.…”
Section: Towards the Futurementioning
confidence: 99%